Pore scale modeling of the mutual influence of roots and soil aggregation in the rhizosphere - Rötzer, Maximilian; Prechtel, Alexander; Ray, Nadja (Frontiers in Soil Science, 2023)
Investigating plant/root-soil interactions at different scales is crucial to advance the understanding of soil structure formation in the rhizosphere. To better comprehend the underlying interwoven processes explicit, fully dynamic spatial and image-based modeling at the pore scale is a promising tool, especially taking into account experimental limitations. We develop a modeling tool to investigate how soil aggregation, root growth and root exudates mutually interact with each other at the micro-scale. This allows the simultaneous simulation of the dynamic rearrangement of soil particles, the input and turnover of particulate organic matter, root growth and decay as well as the deposition, redistribution and decomposition of mucilage in the rhizosphere. The interactions are realized within a cellular automaton framework. The most stable configuration is determined by the amount and attractiveness of surface contacts between the particles, where organo-mineral associations preferably lead to the formation of soil aggregates. Their break-up can be induced by root growth or the degradation of gluing agents previously created after the decomposition of POM and mucilage. We illustrate the model's capabilities by simulating a life cycle of a fine root in a two-dimensional, horizontal cross section through the soil. We evaluate various scenarios to identify the role of different drivers such as soil texture and mucilage. We quantify the displacement intensity of individual particles and the variations in local porosity due to the change in available pore space as influenced by root growth and observe compaction, gap formation and biopore evolution. The simulation results support that the deposition of mucilage is an important driver for structure formation in the rhizosphere. Although mucilage is degraded within a few days after exudation, it leads to a persistent stabilization of the aggregated structures for both textures in the vicinity of the root within a time frame of 1000 days. Local porosity changes are quantified for for exudation periods of 1, 10 and 100 days and are already pronounced for short-term exudation of mucilage. This stabilization is significantly different from the structures encountered when only POM could trigger the evolution of gluing spots, and is still present after complete degradation of the root.